(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This research is aiming to try to find out the impacts of quality which represented by its removal in the service provided to the client . Mabrouka cement factory was option as a place for the study. As the study consisted of two variables, namely: the quality represented by its dimensions (performance, reliability, conformity, organization) as an independent variable, and client service as a dependent variable. That the importance of the study lies in determining which of the aforesaid dimensions have the greatest effect on the service which provided to the client, the research was based on two thesis . The first thesis is based on the existence of a correlation and impact relationship between the dimensions of quality combined and client service. The pattern of the questionnaire was used in order to reach the inference and recommendations of the research also in arrangement to reach the final results of the reconnaissance, then use the statistical program (spss) to analyze the study data, then the correlation coefficient and multiple linear retreating were used from the analysis of the specimen answers as statistical tools.